2008
DOI: 10.1016/j.anireprosci.2007.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of bovine preantral follicle viability and ultra-structure after cooling and freezing of ovarian tissue

Abstract: Bovine preantral follicles within ovarian fragments were exposed and cryopreserved in absence or presence of 1.5 M glycerol (GLY), ethylene glycol (EG), propanediol (PROH) or dimethyl sulfoxide (DMSO), undergoing a previous cooling at 20 °C for 1 h (protocol 1) or at 4 °C for 24 h (protocol 2) in 0.9% saline solution. At the end of each treatment, preantral follicles were classified as non-viable/viable when they were stained/not stained with trypan blue, respectively. To confirm viability staining, ultra-stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 25 publications
1
15
0
3
Order By: Relevance
“…In that regard, the latter was closely related to the organization of ovarian tissue and associated with species-specific characteristics [32], not allowing for extrapolation of protocols for species that are phylogenetically distant.…”
Section: Discussionmentioning
confidence: 99%
“…In that regard, the latter was closely related to the organization of ovarian tissue and associated with species-specific characteristics [32], not allowing for extrapolation of protocols for species that are phylogenetically distant.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previous studies have shown the value of antioxidants in protecting ovarian tissue from ischemia following transplantation (Kim et al 2004) or their usefulness in freezing medium to improve follicular preservation (Melo et al 2011;Sanfilippo et al 2013). Vacuolization has been reported after cryopreservation of ovarian tissue from sheep (Santos et al 2006b;Oskam et al 2010), bovine (Celestino et al 2008) and human (Marsella et al 2008), with indications of damage in the ER (Silva et al 2000). In agreement with this evidence, Oskam et al (2010) found oocyte vacuolization together with an extreme decrease in or even total absence of smooth and rough ER in cryopreserved sheep ovarian tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with the results of other groups, who found DMSO to allow for better preservation of primary follicles than PrOH in human tissue (Gandolfi et al 2006), although no effects were found in the population of primordial follicles in that study. Other studies suggest that even though EG is known for its low toxicity when applied as a cryoprotectant of bovine and caprine ovarian tissue (Santos et al 2006b, Celestino et al 2008, DMSO preserves the ultrastructure of ovine early-staged follicles better (Santos et al 2006a).…”
Section: Discussionmentioning
confidence: 99%